Gestational hyperglycemia and the risk of cardiovascular diseases among elderly Chinese women: Findings from the REACTION study. Issue 12 (6th September 2021) - Hu, Chunyan; Zhang, Yi; Lin, Lin; Wang, Shuangyuan; Du, Rui; Zhang, Jie; Qi, Hongyan; Li, Mian; Zhu, Yuanyue; Huo, Yanan; Wan, Qin; Qin, Yingfen; et al.
Abstract: Background: Gestational hyperglycemia increases the risk of diabetes in later life. However, the risk of future cardiovascular diseases (CVD) related to gestational hyperglycemia remains inconclusive. The purpose of this study was to investigate the impact of gestational hyperglycemia on the subsequent risk of CVD and its modifying factors among elderly Chinese women. Methods: We conducted a case‐control study of elderly women from the baseline survey of Risk Evaluation of cAncers in Chinese diabeTic Individuals: a lONgitudinal (REACTION) study. Women with gestational hyperglycemia (n = 82), and controls matched by age and study site (n = 410) were included. Information on CVD, including reported coronary heart disease, stroke, or myocardial infarction, was collected through an interviewer‐assisted questionnaire. Results: Women with gestational hyperglycemia were more likely to develop diabetes (odds ratio [OR], 2.51; 95% confidence interval [CI], 1.50‐4.18) and CVD (OR, 1.98; 95% CI, 1.05‐3.74). Even without progressing to type 2 diabetes, gestational hyperglycemia was associated with an increased risk of CVD (OR, 2.88; 95% CI, 1.18‐7.00). However, subgroup analysis indicated that compared with those without gestational hyperglycemia or hypertension, women with both gestational hyperglycemia and hypertension had higher risk of CVD (OR, 3.98; 95% CI, 1.65‐9.58), whereas the risk estimate did not significantly change in women with gestational hyperglycemia alone (OR, 2.15; 95% CI, 0.71‐6.57). Stratified analysis indicated that among those with overweight/obesity, inactive physical activity, or unhealthy dietary habits, gestational hyperglycemia increased the risk of CVD. Conclusions: In elderly Chinese women, gestational hyperglycemia was associated with an increased risk of CVD in later life. This association was independent of the progression to diabetes and might be modified by lifestyle factors and hypertension. Abstract : Highlights Even without progressing to type 2 diabetes, gestational hyperglycemia is associated with an increased risk of cardiovascular disease (CVD). The association between gestational hyperglycemia and CVD risk could be modified by lifestyle factors and hypertension. Subsequent blood pressure management and lifestyle intervention for women with gestational hyperglycemia are important approaches to prevent CVD. 摘要: 背景: 妊娠高血糖会增加以后患糖尿病的风险。然而，与妊娠高血糖相关的未来心血管疾病(Cardiovascular diseases, CVD)的风险仍然不确定。本研究旨在探讨妊娠高血糖对中国老年女性后续心血管疾病风险的影响及其可能的影响因素。 方法: 我们在中国2型糖尿病患者恶性肿瘤发生风险的流行病学(REACTION)研究的老年妇女中开展了一项病例对照研究。研究纳入82名妊娠高血糖女性及410名按年龄和研究中心匹配的对照女性。心血管疾病信息(包括冠心病、中风和心肌梗死)通过调查员辅助的标准化问卷收集。 结果: 有妊娠高血糖的女性更容易发生糖尿病 [比值比(Odd ratio, OR)，2.51； 95%可信区间(Confidence interval, CI)，1.50‐4.18] 和CVD(OR，1.98； 95%CI，1.05‐3.74)。即使没有进展为 2 型糖尿病，妊娠高血糖也与 CVD 风险增加相关(OR，2.88；95%CI，1.18‐7.00)。然而，亚组分析表明，与没有妊娠期高血糖或高血压的女性相比，同时有妊娠期高血糖和高血压的女性患心血管疾病的风险更高(OR，3.98；95%CI，1.65‐9.58)，而CVD风险在单纯有妊娠高血糖的女性中没有显著变化(OR，2.15；95%CI，0.71‐6.57)。分层分析表明，在超重/肥胖、缺乏体力活动或饮食不健康的人群中，妊娠高血糖会显著增加CVD风险。 结论: 在中国老年女性中，妊娠期高血糖与晚年 CVD 风险增加有关。这种关联与是否发展为糖尿病无关，而可能会受到生活方式和高血压的影响。